Chitosan-based nanoparticles as a dual drug delivery system directed to bone infection therapy - Falcão, J. (2022)
Osteomyelitis treatment is usually described as a challenging issue, mainly because of the necessity of high levels of antimicrobials employed for extended periods, since the infection is characterized by poor blood circulation. Innovative options of targeted and controlled drug delivery systems, presenting sustained antimicrobial release, high concentrations of drugs in the infected areas, low concentrations in the bloodstream, and promotion of osteogenesis, need to be considered.